1990
DOI: 10.2331/suisan.56.1083
|View full text |Cite
|
Sign up to set email alerts
|

Otolith daily increment in sandfish.

Abstract: In order to establish the ageing technique of the sandfish Arctoscopus japonicus the deposition rate of otolith increments was determined through time marking by immersing larvae in 400mg/l tetracycline hydrocholride (TC) solution for 24h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Eye pigmentation of H. sajori was observed before hatching and the number of growth increments was almost equal to the known age in days plus 2. This result agrees with Atlantic salmon (Geffen, 1983), Pacific saury (Watanabe and Kuji, 1991) and Japanese sandfish (Tsukamoto and Shima, 1990), which during the embryo stage of these species already form the daily increment that their eye pigment has observed before hatching. On the other hand, in bastard halibut (Tanaka et al, 1985), and Japanese anchovy (Tsuji and Aoyama, 1984) the daily increment is formed a few days after fertilization.…”
Section: Discussionsupporting
confidence: 91%
“…Eye pigmentation of H. sajori was observed before hatching and the number of growth increments was almost equal to the known age in days plus 2. This result agrees with Atlantic salmon (Geffen, 1983), Pacific saury (Watanabe and Kuji, 1991) and Japanese sandfish (Tsukamoto and Shima, 1990), which during the embryo stage of these species already form the daily increment that their eye pigment has observed before hatching. On the other hand, in bastard halibut (Tanaka et al, 1985), and Japanese anchovy (Tsuji and Aoyama, 1984) the daily increment is formed a few days after fertilization.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulation of the basic data about the biology of the larvae and juveniles is important in order to develop these techniques. Some information on growth, otolith daily increment, morphological development and feeding of the larvae and juveniles have been reported 5–9 . This paper reports the fish size and morphological features of reared Japanese sandfish at the onset of burying themselves in the sand under experimental conditions.…”
Section: Frequency Distribution Of Standard Length Of the Japanese Samentioning
confidence: 99%
“…Some information on growth, otolith daily increment, morphological development and feeding of the larvae and juveniles have been reported. [5][6][7][8][9] This paper reports the fish size and morphological features of reared Japanese sandfish at the onset of burying themselves in the sand under experimental conditions. Fertilized eggs were obtained from the Akita Prefectural Fisheries Promoting Center on 15 December 1998.…”
mentioning
confidence: 99%
“…Species with long embryonic periods have been reported to start forming increments in the otoliths before hatching (Geffen, 1983;Tsukamoto and Shima, 1990;Narimatsu and Munehara, 1997;Morales-Nin, 2000;Joh et al, 2008;Nakaya et al, 2008). Most of these workers reported that the prominent increment (check) was associated with eye-pigmentation, but has been shown to form at the time of hatching in fat greenling Hexagrammos otakii (Joh et al, 2008), which is a closely-related species of Arabesque greenling P. azonus.…”
Section: Relationship Between the Morphological Development In Embryomentioning
confidence: 99%
“…In general, fish with long embryonic periods start forming increments in the otoliths before hatching (Geffen, 1983;Tsukamoto and Shima, 1990;Narimatsu and Munehara, 1997;Morales-Nin, 2000;Joh et al, 2008;Nakaya et al, 2008). However there is no detailed information on the relationship between morphological development during the embryonic period and the formation of the otolith microstructure.…”
Section: Introductionmentioning
confidence: 99%